Criminal justice theory: explanations and effects - Chouhy, Cecilia; Cochran, Joshua C.; Jonson, Cheryl Lero; Beckett, Katherine (Advances in criminological theory, 2020)
"Criminal Justice Theory: Explanations and Effects undertakes a systematic study of theories of the criminal justice system, which historically have received very little attention from scholars. This is a glaring omission given the risk of mass imprisonment, the increasing presence of police in inner-city communities, and the emergence of new policy initiatives aimed at improving the quality and effectiveness of the administration of justice. Fortunately, however, a number of disparate theoretical works have appeared that seek to provide insight into the nature and impact of criminal justice. Based on 14 original essays by influential scholars, this volume pulls together the most significant of these perspectives, thus creating a state-of-the-art assessment of contemporary criminal justice theory. Criminal justice theory can be divided into two main categories. The first includes works that seek to explain the operation of the criminal justice system. Most of these contributions have grappled with the core reality of American criminal justice: its rising embrace of punitiveness and the growth of mass imprisonment. The second category focuses on works that identify theories that have often guided efforts to reduce crime. The issue here focuses mainly on the effects of certain theoretically guided criminal justice interventions. The current volume is thus organized into these two categories: explanation and effects. The result is an innovative and comprehensive book that not only serves researchers by advancing scholarship but also is appropriate for advanced undergraduate or graduate classroom use"--